Evaluation of the Success of the Academic Information System at STMIK Bina Bangsa Kendari Using the DeLone & McLean Model - Rahmat Inggi; Minson Simatupang; Adris Ade Putra; La Ode Muh. Nurrakhmad Arsyad (Jurnal Armada Informatika, 2026)
This study aims to evaluate the success of the Academic Information System (SIAKAD) implementation at STMIK Bina Bangsa Kendari using the DeLone & McLean model. This model measures information system success through six main variables, namely System Quality, Information Quality, Service Quality, Use, User Satisfaction, and Net Benefit. This research employs a quantitative approach using a survey method by distributing questionnaires to students as the primary users of the system. The sampling technique used is simple random sampling, with a total of 259 respondents. The collected data were analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with the assistance of SmartPLS software. The results indicate that System Quality and Information Quality have a significant effect on both Use and User Satisfaction. Meanwhile, Service Quality does not significantly affect Use but has a significant effect on User Satisfaction. Furthermore, the variables Use and User Satisfaction are proven to have a significant effect on Net Benefit. The R-Square values indicate that the model has a good capability in explaining the dependent variables, particularly user satisfaction and system benefits. Overall, the findings reveal that the success of SIAKAD is strongly influenced by system quality, information quality, and user satisfaction. Therefore, improving system and information quality, as well as strengthening technical support services, are essential factors in enhancing the benefits of academic information systems in higher education institutions.